Characterization on the effect of electrospinning parameters on polyacrylonitrile (Pan) - Nurul Azni Binti Bakaruddin (School of Material Engineering, University Malaysia Perlis, 2016)
This research focuses on characterization on the effect of electrospinning parameters on polyacrylonitrile (PAN). Polyacrylonitrile (PAN) is used as the main materials in this research. PAN undergoes electrospinning process to produce PAN fiber. Electrospinning of PAN was done at different parameters which were flow rate (5L/min, 7L/min and 9L/min), concentration (8 wt%, 10 wt% and 12 wt%) and distance between the syringe and collector (8cm, 10cm, 12cm). A systematic study of a polyacrylonitrile was characterized by using Scanning Electron Microscope (SEM), thermogravimetric Analysis (TGA) and electrical conductivity. Each parameter gives its own pattern for the results. For PAN fibre with different concentration, the diameter of the PAN fibre with the highest concentration which is 12 wt% has the largest diameter compared to the other two concentration which are 8 wt% and 10 wt%. PAN fibre with different flow rate also gives the same result as different concentration. PAN fibre with highest flow rate which 9L/min has the largest diameter with value 1.05. Meanwhile, the result for PAN fibre with different distance between the syringe and the tip of the collector shows different pattern. The lowest value of the distance which is 8cm will produce PAN fiber with high diameter which is 1.14.